Impact of HR Practices on Organizational Performance in Bangladesh - Absar, M.M.N.; Nimalathasan, B.; Jilani, M.M.A.K. (My University, 2010)
Impact of human resource management practices on organizational performance has been a widely researched area for years. But unfortunately, very insuficient number of studies have been conducted on this area in the context of Bangladesh and other developing countries. This study was undertaken to ill this obvious research gap. Data collected from ifty manufacturing irms in Bangladesh shows that HR practices have signiicant association with organizational performance. Out of HR practices, only performance appraisal is found to have signiicant impact on organizational performance.
Keywords: HR Practices; Organizational Performance; Manufacturing Firms